satellite-based rice monitoring system in Cambodia and Vietnam - CGIAR Research Program on Rice (2018)
The application of the technology in the Philippines is serving as a model for other countries in Asia, specifically Cambodia and Vietnam, where discussions on institutionalization of the technology are on-going